2014
DOI: 10.4236/sm.2014.44029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wealth Inequality on Higher Education Outcomes: A Critical Review

Abstract: American society reflects considerable class immobility, much of which may be explained by the wide gaps in college completion rates between economically advantaged and disadvantaged groups of students. First, we discuss the factors that lead to unequal college completion rates and introduce assets as an explanation often ignored by stratification scholars. We then discuss how a legacy of wealth inequality has led to wealthy students having an advantage at the financial aid bargaining table over low-income and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…Students from financially poorer backgrounds are reported as experiencing multiple educational disadvantage, which impacts upon student choices, decisions and experiences in relation to university attendance (Terenzini, Cabrera & Bernal, 2001). For example, research has shown that these students are not only disadvantaged in terms of unequal access to financial resources but also they may be particularly averse to taking on student debt (Rauscher & Elliott III, 2014). Within Australia, concern tends to centre on the costs associated with living expenses and travel (Rasmussen, 2006;Rauscher & Elliott, 2014) whereas in the US and the UK there is more unease about the impact of tuition fees (Banks-Sontilli, 2014;Jones, 2016).…”
Section: First-in-family Students Poverty and University Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Students from financially poorer backgrounds are reported as experiencing multiple educational disadvantage, which impacts upon student choices, decisions and experiences in relation to university attendance (Terenzini, Cabrera & Bernal, 2001). For example, research has shown that these students are not only disadvantaged in terms of unequal access to financial resources but also they may be particularly averse to taking on student debt (Rauscher & Elliott III, 2014). Within Australia, concern tends to centre on the costs associated with living expenses and travel (Rasmussen, 2006;Rauscher & Elliott, 2014) whereas in the US and the UK there is more unease about the impact of tuition fees (Banks-Sontilli, 2014;Jones, 2016).…”
Section: First-in-family Students Poverty and University Participationmentioning
confidence: 99%
“…For example, research has shown that these students are not only disadvantaged in terms of unequal access to financial resources but also they may be particularly averse to taking on student debt (Rauscher & Elliott III, 2014). Within Australia, concern tends to centre on the costs associated with living expenses and travel (Rasmussen, 2006;Rauscher & Elliott, 2014) whereas in the US and the UK there is more unease about the impact of tuition fees (Banks-Sontilli, 2014;Jones, 2016). While this difference in emphasis may reflect the variations in student funding arrangements across countries, the commonality of debt-aversion is reported across the international higher education environment.…”
Section: First-in-family Students Poverty and University Participationmentioning
confidence: 99%
“…But low-income students have unequal chances of completing a degree. On the other hand, a legacy of wealth inequality gives wealthy students an advantage at the financial aid bargaining table over low-income and minority students [12,13].…”
Section: Social Inequality and Higher Educationmentioning
confidence: 99%
“…Rauscher & Elliott [13] posit that education can increase opportunity, but how much education one attains depends strongly on their socioeconomic standing. They argue that education both reduces and reproduces inequality, transmitting advantages from one generation to the next.…”
Section: Social Inequality and Higher Educationmentioning
confidence: 99%
“…However, study success and high achievements may reflect students' well-being and health, too (Eide & Showalter, 2011;. Well-being makes study processes smoother (Rauscher & Elliott III, 2014), but on the other hand, if studies become prolonged or overwhelming, students' quality of life decreases .…”
Section: Study Success Tells About Well-being Toomentioning
confidence: 99%